(untitled) (Studia Doctoralia Psychology and Educational Science, 2025)
This study examines the psychometric validity of the IDEA-R scale through exploratory (EFA) and confirmatory factor analyses (CFA), evaluating the essential traits of emerging adulthood (18–25 years). IDEA-R was administered to a sample of 243 participants (M = 21.6, SD = 2.23), 77% of whom were women. The objectives included identifying the latent structure of the instrument and confirming it using advanced statistical methods. EFA revealed four main factors: identity exploration, practical autonomy, independence, and transition to maturity. CFA confirmed a moderate model fit (CFI = .812, RMSEA = .0926), suggesting the need for theoretical refinements. IDEA-R demonstrated high internal consistency (Cronbach’s Alpha = .869), indicating adequate reliability for assessing the psychosocial characteristics specific to this developmental stage. The results highlight the complexity of identity and transitional processes during emerging adulthood, providing a foundation for tailored interventions.